Quantum chemical investigation of the effect of alkali metal ions on the dynamic structure of water in aqueous solutions. Issue 39 (16th September 2022) - Khanal, Rabi; Irle, Stephan
Abstract : Cation size primarily governs dynamic correlations in aqueous solutions. However, drawing a clear line between chaotropic and cosmotrope ions is complicated by the fact that all cations delay dynamic correlation decay. Abstract : We report quantum chemical molecular dynamics (MD) simulations based on the density-functional tight-binding (DFTB) method to investigate the effect of K +, Na +, and Mg 2+ ions in aqueous solutions on the static and dynamic structure of bulk water at room temperature and with various concentrations. The DFTB/MD simulations were validated for the description of ion solvation in aqueous ionic solutions by comparing static pair distribution functions (PDFs) as well as the cation solvation shell between experimental and available ab initio DFT data. The effect of the cations on the water structure, as well as relative differences between K +, Na +, and Mg 2+ cations, were analyzed in terms of atomically resolved PDFs as well as time-dependent Van Hove correlation functions (VHFs). The investigation of the VHFs reveals that salt ions generally slow down the dynamic decay of the pair correlations in the water solvation sphere, irrespective of the cation size or charge. The analysis of partial metal–oxygen VHFs indicates that there are long-lived correlations between water and Na + over long distances, in contrast to K + and Mg 2+ .